A Functional-Stylistic Study of Iconicity in Niyi Osundare’s Waiting Laughters (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
The principle of iconicity maintains that language, for all its arbitrariness, is an iconic mirror of reality. The iconic use of language is a pronounced feature of poetry, especially in Osundare’s art. This study is a functional-stylistic analysis of iconic features in Osundare’s Waiting Laughters. A careful analysis of the grapho-syntactic patterns in the texts showed his conscious efforts to capture experiences through the form of his art. Specifically, findings in the study showed that three dominant features namely indentational highlighting, lexical fragmentation, and anaphora, act as a powerful rhythmic undercurrent which signal the message of the text - the rickety and ramshackle state of physical and socio-economic infrastructures in Nigeria and the overwhelming atmosphere of tortuous waiting (in vain?) for a better nation. The paper concluded that with the mimetic capability of these iconic sequences to produce and sustain meaning connections, the message of the volume attains timelessness, and gains even greater significance now more than ever before as the situation of things in the country cascades from bad to worse.
Keywords: iconicity; stylistics; arbitrariness; mimetic; significance